Analytical study of the acoustic field in a spherical resonator for single bubble sonoluminescence - Dellavale Clara, Hector Damian (2009)
The acoustic ﬁeld in the liquid within a spherical solid shell is calculated. The proposed model takes into account Stoke?s wave equation in the viscous ﬂuid, the membrane theory to describe the solid shell motion and the energy loss through the external couplings of the system. A point source at the resonator center is included to reproduce the acoustic emission of a sonoluminescence bubble. Particular calculations of the resulting acoustic ﬁeld are performed for viscous liquids of interest in single bubble sonoluminescence. The model reveals that in case of radially symmetric modes of low frequency, the quality factor is mainly determined by the acoustic energy ﬂowing through the mechanical coupling of the resonator. Alternatively, for high frequency modes the quality factor is mainly determined by the viscous dissipation in the liquid. Furthermore, the interaction between the bubble acoustic emission and the resonator modes is analyzed. It was found that the bubble acoustic emission produces local maxima in the resonator response. The calculated amplitudes and relative phases of the harmonics constituting the bubble acoustic environment can be used to improve multi-frequency driving in sonoluminescence.